Disaster talk: The increased knowledge of disaster management among a study group of students of Faculty X University Y - Fandita Tonyka Maharani; Dyah Utari (Community Empowerment, 2022)
Indonesia has been known as a disaster-prone country. Disasters can occur due to several things, namely natural disasters, disasters due to technological failures, and also emerging risks. Disaster control can be done by knowing disaster management in an integrated and comprehensive manner. Providing information and increasing relevant knowledge about disasters is one of the implementations of the disaster management phase, namely the pre-disaster stage. University students are chosen as partners because they are agents of change who can play a significant role in society. The method of implementing community service is through online lectures and discussions. Pre and post-test were carried out to determine the comparison of knowledge in students. This activity succeeded in increasing students' knowledge about disaster management.